دراسة حساسية بعض أصناف التبغ لمرض الساق الأسود المتسبب عن الفطرPhytophthora parasitica var. nicotianae تحت ظروف العدوى الطبيعية والاصطناعية في محافظة طرطوس - حسن, محمود; علاف, عصام; حسن, طارق (Latakia University Journal -Biological Sciences Series, 2019)
يهدف البحث إلى دراسة حساسية بعض أصناف التبغ[ البلدي, البرلي , الفرجينيا] المزروعة في الساحل السوري (محافظة طرطوس) لمرض الساق الأسود المتسبب عن الفطر: Phytophthora parasitica var. nicotianae. نفِّذ مسح حقلي في 14 موقعاً في محافظة طرطوس والموزعة على ارتفاعات ما بين 18-980م خلال الموسمين الزراعيين 2007 و 2008 . وبيّنت النتائج أن جميع الأصناف التي شملتها الدراسة كانت قابلة للإصابة بالمرض وأعلى نسبة للإصابة في أصناف البلدي والبرلي والفرجينيا لموسم 2007 كانت 10%, 88.%, 8.1% على التوالي, وكانت شدة الإصابة 3.5%, 2.5%, 2.4% على التوالي. أما في الموسم التالي 2008 فكانت نسبة الإصابة 12.5%, 10.7%, 8.8% على التوالي وشدَّة الإصابة 4.1%, 3.3%, 2.7% على التوالي. مما يدل (حقلياً) على أن الصنفين البرلي والبلدي أكثر قابلية للإصابة من الصنف فرجينيا . أظهرت نتائج العدوى الاصطناعية أن نسبة الإصابة في الأصناف المختبرة قد بلغت 70% للصنف البلدي (شك البنت) و75 % للبرلي و45% للفرجينيا, وكان متوسط شدة الإصابة 29 , 26 , 13 على التوالي. مما يؤكد نتائج المسح الحقلي أن مرض الساق الأسود يصيب الأصناف الثلاثة المزروعة في الساحل السوري ويعتبر الفرجينيا أقل قابلية للإصابة من صنفي البرلي والبلدي. The aim of this study is to define the sensitivity of some tobacco varieties [Al-Balady, Burley, Fergenia] planted in the Syrian seacoast (Tartous governorate) to black shank disease which is caused by the fungus: Phytophthora parasitica var. nicotianae. A field survey was conducted on 14 sites in Tartous governorate with different heights ranging between 18 and 980m during 2007 & 2008. The results in 2007 showed infection percentages of Al- Balady, Burley and Fergenia: 10%, 8.8% and 8.1% respectively, and average of infection: 3.5%, 2.5%, and 2.4% respectively. In the next year 2008 the infection percentages of the three varieties were: 12.5%, 10.7% and 8.8% and the average of infection: 4.1%, 3.3%, and 2.7% respectively. This indicated that the two varieties Al-Balady and Burley were more sensitive to infection in the field than Fergenia. The results of artificial infection showed the average of infection percentages of tested varieties was: Al-Balady 70%, Burley 75% and 45% to Fergenia and this confirms the field's survey results. The average of infection was: 29, 26 and 13 % to the Burley, Al-Balady, Fergenia varieties respectively. It could be concluded that Black Shank Disease can infect the three varieties which are grown in the Syrian coastal region, with Fergenia being less sensitive to infection than the other two varieties, Al-Balady and Burley.